2021
DOI: 10.1016/j.esmoop.2021.100161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing, technique and molecular features on brain control with local therapies in oncogene-driven lung cancer

Abstract: Background The improved efficacy of tyrosine kinase inhibitors (TKI) mandates reappraisal of local therapy (LT) for brain metastases (BM) of oncogene-driven non-small-cell lung cancer (NSCLC). Patients and methods This study included all epidermal growth factor receptor-mutated (EGFR + , n = 108) and anaplastic lymphoma kinase-rearranged (ALK + , n = 33) TKI-naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
3
12
0
Order By: Relevance
“…In our study, we did not observe a significant difference in icORR or iPFS between the WBRT and SRS subgroups, which might be related to data volume limitations. Similar results were obtained in a retrospective study that included 179 driver gene mutation-positive NSCLC patients with BM who received TKIs combined with RT; that is, WBRT did not offer better intracranial control than SRS, and this was probably related to the better systematic tumor control with TKI and ICI compared with pure chemotherapy ( 60 ). Another possible reason is the impact of the number of BMs.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, we did not observe a significant difference in icORR or iPFS between the WBRT and SRS subgroups, which might be related to data volume limitations. Similar results were obtained in a retrospective study that included 179 driver gene mutation-positive NSCLC patients with BM who received TKIs combined with RT; that is, WBRT did not offer better intracranial control than SRS, and this was probably related to the better systematic tumor control with TKI and ICI compared with pure chemotherapy ( 60 ). Another possible reason is the impact of the number of BMs.…”
Section: Discussionsupporting
confidence: 76%
“…Ni et al found that upfront brain radiotherapy before crizotinib for patients with advanced ALK-positive NSCLC postpones disease progression (30). Analogically, Shafie et al observed a better intracranial progression-free survival in TKI-treated EGFR/ALK mutant NSCLC treated with early local therapy, regardless of the radiotherapy technique (31). A retrospective analysis observed that the mPFS was 36 months in the LCT plus TKI group and 14 months in the TKI-only group in metastatic NSCLC (32).…”
Section: Discussionmentioning
confidence: 98%
“…platinum-based chemotherapy and EGFR inhibitors ( 21 ), therefore brain involvement appears to be an adverse prognostic factor for this patient group under several different therapies. Thus, use of mobocertinib in patients with brain metastases will require complementary use of radiotherapy in order to extend the intracranial PFS, as is also standard for patients with other oncogene-driven NSCLC beyond the first line ( 22 ). At the same time the ORR under mobocertinib was clearly superior to that of current alternatives, such as monochemotherapy and EGFR inhibitors, which both showed ORR of 0-10% in real-world studies of pretreated patients with EGFR exon20ins ( 21 ).…”
Section: Discussionmentioning
confidence: 99%